Front Cover: An Extended Approach for the Development of Fluorogenic trans‐Cyclooctene–Tetrazine Cycloadditions (ChemBioChem 7/2019). (6th March 2019) - Siegl, Sebastian J.; Galeta, Juraj; Dzijak, Rastislav; Vázquez, Arcadio; Del Río‐Villanueva, Miguel; Dračínský, Martin; Vrabel, Milan
Abstract : The front cover picture shows two different dihydropyridazine fluorophores formed in the inverse‐electron‐demand Diels–Alder reaction of 1, 2, 4, 5‐tetrazines with two different trans ‐cyclooctene (TCO) isomers. A very small structural change in the starting TCO leads to the formation of two different dihydropyridazine tautomers with distinct photophysical properties. The older version of this reaction (blue‐emitting tautomer) was extended to various TCO derivatives, thereby providing access to new dyes with improved properties. This fluorogenic bioorthogonal reaction was successfully applied to label cell membranes and intracellular compartments. More information can be found in the communication by M. Vrabel et al. on page 886 in Issue 7, 2019 (DOI: 10.1002/cbic.201800711 ).